Quantifying the Relationship Between Self-Efficacy and Mathematical Creativity: A Meta-Analysis - Herianto Herianto; Anastasia Sofroniou; Muh Fitrah; Dadan Rosana; Caly Setiawan; Raden Rosnawati; Widihastuti Widihastuti; Andi Jusmiana; Yudince Marinding (Education Sciences)
This study is a meta-analysis to examine the relationship between self-efficacy and mathematical creativity. This meta-analysis included 21 studies with a total sample size of 11,621 participants and 33 effect sizes across the studies. Data analysis using a random effects model using the “meta” package (version 7.0-0) in R software version 4.3.0. The results showed a positive and significant relationship between self-efficacy and mathematical creativity <semantics>(z=3.51;95% CI [0.09, 0.32], p<0.001</semantics>). The influence of self-efficacy on mathematical creativity is included in the low category (<semantics>re=0.21</semantics>). These findings had no publication bias issues with Egger’s test (<semantics>t=−0.03; p=0.978</semantics>) and were stable against the impact of unpublished studies (<semantics>Fail−safe N=5101; p<0.001</semantics>). Meta-regression revealed two variables that showed significant results: measurement method (<semantics>Q=11.17;df=2; p=0.0038</semantics>) and study location (<semantics>Q=372.41, df=9; p<0.0001</semantics>). This study provides valuable information about the relationship between self-efficacy and mathematical creativity, but more research is needed to develop effective and efficient learning strategies.